Characterization of Mortality from Diabetes Mellitus in Cienfuegos Province during the First Nine Months of 2020 - Isis Arelis Espinosa Salas; Sara Hernández Malpica; Lourdes Elena Duany Badell; Bárbara Zabala Enrique; Yusimí Cabada Martínez; Leticia Castro Morejón (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: according to the World Health Organization, diabetes causes 300,000 deaths a year in Latin America and the Caribbean and in the Cienfuegos province since 2020 it ranks as the seventh cause of death. Objective: to characterize mortality from diabetes mellitus in the Cienfuegos province in the first nine months of 2020. Methods: a descriptive investigation was carried out on health systems and services based on a series of cases to characterize mortality from diabetes mellitus in Cienfuegos in the first nine months of 2020. The deceased were compiled taking into account: sex, age, skin color, educational level, place of residence, territorial stratum, disease, associated risk factors and direct causes of death. The arithmetic mean and standard deviation were used. The results are presented in the form of tables and graphs. Results: the greatest affectation was in the last decades of life for the female gender, as well as residence in an urban territory, among the first direct causes of death are pulmonary thromboembolism, as well as acute chronic renal failure; hydroelectrolytic imbalance stands out in a considerable number of deaths. Conclusions: the last decades of life were the most affected and the female sex, the main causes of death were: pulmonary thromboembolism and acute chronic renal failure. The hydroelectrolytic imbalance stands out in a considerable number of the deceased.